Cardiac metastasis of tongue squamous cell carcinoma complicated by pulmonary embolism: A case report. Issue 28 (July 2017) - Malekzadeh, Sonaz; Platon, Alexandra; Poletti, Pierre-Alexandre
Abstract: Rationale: Cardiac metastasis is known as a rare complication of head and neck malignancy. Patient concerns: We present a 58-year-old woman patient with a history of tongue carcinoma who was admitted in emergency department for sudden chest pain. Imaging work-up by computed tomography (CT) and positron emission tomography-computed tomography (PET-CT) diagnosed a cardiac metastasis complicated by intraventricular thrombus and pulmonary embolism. Diagnosis: Cardiac metastasis from tongue carcinoma complicated by pulmonary embolism. Interventions: After undergoing 2 cycles of palliative chemotherapy, the patient declined any further treatment. Outcomes: Patient died 3 months after the diagnosis of cardiac metastasis. Lessons: Cardiac metastasis should be considered as a differential diagnosis in patients with a history of head and neck malignancy who present non-specific cardiac symptoms.